A Molecular Imaging Approach to Mercury Sensing Based on Hyperpolarized 129Xe Molecular Clamp Probe. Issue 12 (2nd February 2016) - Guo, Qianni; Zeng, Qingbin; Jiang, Weiping; Zhang, Xiaoxiao; Luo, Qing; Zhang, Xu; Bouchard, Louis‐S.; Liu, Maili; Zhou, Xin
Abstract: Mercury pollution, in the form of mercury ions (Hg 2+ ), is a major health and environmental hazard. Commonly used sensors are invasive and limited to point measurements. Fluorescence‐based sensors do not provide depth resolution needed to image spatial distributions. Herein we report a novel sensor capable of yielding spatial distributions by MRI using hyperpolarized 129 Xe. A molecular clamp probe was developed consisting of dipyrrolylquinoxaline (DPQ) derivatives and twocryptophane‐A cages. The DPQ derivatives act as cation receptors whereas cryptophane‐A acts as a suitable host molecule for xenon. When the DPQ moiety interacts with mercury ions, the molecular clamp closes on the ion. Due to overlap of the electron clouds of the two cryptophane‐A cages, the shielding effect on the encapsulated Xe becomes important. This leads to an upfield change of the chemical shift of the encapsulated Xe. This sensor exhibits good selectivity and sensitivity toward the mercury ion. This mercury‐activated hyperpolarized 129 Xe‐based chemosensor is a new concept method for monitoring Hg 2+ ion distributions by MRI. Abstract : In a pinch : A novel sensor is reported that is capable of yielding spatial distributions of mercury ions by MRI, using hyperpolarized 129 Xe. This clamp probe (see figure) consists of dipyrrolylquinoxaline (DPQ) derivatives and two cryptophane‐A cages. The DPQ derivatives act as cation receptors, whereas cryptophane‐A acts as a suitable host molecule for xenon. This sensor exhibits good selectivity and sensitivity toward the mercury ions.